BRITE-Constellation photometry of π5 Orionis, an ellipsoidal SPB variable. Issue 2 (12th June 2020) - Jerzykiewicz, M; Pigulski, A; Handler, G; Moffat, A F J; Popowicz, A; Wade, G A; Zwintz, K; Pablo, H
ABSTRACT: Results of an analysis of the BRITE-Constellation photometry of the SB1 system and ellipsoidal variable π 5 Ori (B2 III) are presented. In addition to the orbital light-variation, which can be represented as a five-term Fourier cosine series with the frequencies f orb, 2 f orb, 3 f orb, 4 f orb, and 6 f orb, where f orb is the system's orbital frequency, the star shows five low-amplitude but highly significant sinusoidal variations with frequencies fi ( i  = 2, .., 5, 7) in the range from 0.16 to 0.92 d −1 . With an accuracy better than 1σ, the latter frequencies obey the following relations: f 2 − f 4  = 2 f orb, f 7 − f 3  = 2 f orb, f 5  = f 3 − f 4  = f 7 − f 2 . We interpret the first two relations as evidence that two high-order ℓ = 1, m  = 0 gravity modes are self-excited in the system's tidally distorted primary component. The star is thus an ellipsoidal SPB variable. The last relations arise from the existence of the first-order differential combination term between the two modes. Fundamental parameters, derived from photometric data in the literature and the Hipparcos parallax, indicate that the primary component is close to the terminal stages of its main-sequence (MS) evolution. Extensive Wilson–Devinney modelling leads to the conclusion that best fits of the theoretical to observed light curves are obtained for the effective temperature and mass consistent with the primary's position in the HR diagram and suggests that the secondary is in an early MS evolutionary stage.